Item Sequencing and Academic Performance in Physics: A Quasi -Experimental Approach with Gender and Test Anxiety as Control Variables - Ofem, Usani; Ovat, Sylvia; Hycenth, Ntah; Udeh, Maryrose (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study seeks to examine the effect of item sequencing on academic performance using the control variables of gender and test anxiety. Methodology: A total of 245 participants were used for the study. Two instruments, the Test Anxiety Inventory (TAI) developed by Spielberger in 1980 and the Physics Achievement Test (PAT) developed by Ibout in 2022, were used for data collection. The collected data were analysed using means, standard deviations, and analysis of covariance (ANCOVA). Findings: The result showed that gender significantly influences students’ performance in physics. Emotional test anxiety has a significant effect on test performance in Physics and item sequencing has a significant effect on post-test performance in Physics. The result further showed that no interactive effect exists between item sequencing and the dimension of test anxiety assessed on the post-test score in Physics. Conclusion: Based on the result that are obtained for this study, it is evident that gender has a significant effect on student performance in Physics. Test anxiety (emotional test anxiety has a n effect on students score in the post test vin Physics and items sequence influences students’ performance a s well. More so, there is no interactive effect of gender, anxiety, and items sequencing on students’ performance in Physics.